2015
DOI: 10.1007/978-3-319-08879-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Assisted Forming

Abstract: The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevant protective laws and regulations and therefore free for general use. While the advice and information in this book are believed to be true and accurate at the date of publication, neither the authors nor the editors nor the publisher can accept any legal responsibility for any errors or omissions that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…Electrons travelling through the material allow an easier motion of dislocations in the same direction. An additional effect occurs when the travelling electrons help to separate and re-form metallic bonds, which increases the materials ductility and makes it more workable [19].…”
Section: Electroplastic Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrons travelling through the material allow an easier motion of dislocations in the same direction. An additional effect occurs when the travelling electrons help to separate and re-form metallic bonds, which increases the materials ductility and makes it more workable [19].…”
Section: Electroplastic Effectmentioning
confidence: 99%
“…The literature also provides a lot of different etchants for Mg-based alloys. The etchants listed in Table 2 [3,18,19] were used for deformed samples of the alloy AZ31, which among others was investigated in this work. This table shows that an important part of the selection process for optimal etching is the use of the same etchant with different concentrations of components.…”
Section: Sample Preparationmentioning
confidence: 99%
“…In respect to metal processing, Molostkii and Fleurov [10] reported the following effects of high-density electric current pulses: Stress reduction during processing, fragility decrease, improvement of surface finishing, variation of values for tensile strength and strain, microstructure changes. The study of the aforementioned effects is known as Electrical Assisted Forming (EAF), one of the first published compilations was presented by Salandro et al [12]. EAF processing relies on the electroplastic effect, where thermal (in micro and macro scale) influences improve deformability of a metallic material [12].…”
Section: Introductionmentioning
confidence: 99%
“…The study of the aforementioned effects is known as Electrical Assisted Forming (EAF), one of the first published compilations was presented by Salandro et al [12]. EAF processing relies on the electroplastic effect, where thermal (in micro and macro scale) influences improve deformability of a metallic material [12]. At atomic level, Spitsyn y Troitskii [15] found that external current pulses generate changes on resistivity of metallographic defects such as boundary grain, dislocations and inclusions; promoting dislocation mobility and modification of mechanical behaviour of material.…”
Section: Introductionmentioning
confidence: 99%
“…Electroplasticity (EP) is a phenomenon in which applied pulsed electric fields during deformation result in increased formability in metals. This phenomenon has been studied since the 1950's [1] and researchers have proposed two possible origins of this nearly-universal effect: (1) localized Joule heating at lattice defects and (2) the electron wind effect leading to vacancy migration [2]. However, there is no clear evidence of the true origin of this behavior at the level of individual defects [3].…”
mentioning
confidence: 99%